DIGITAL PROMOTION USAGE IN CULTIVATING BRAND ENGAGEMENT AMONG MILLENNIALS USERS AT STARBUCKS INDONESIA - Ayuphita Tiara Silalahi; Della Liudi (Bina Nusantara University, 2018)
In reaching the millennials to have a consumer engagement with the Starbucks brand, the giant coffee has globally reaching out to millions of its consumers by way of digital platforms such as Instagram, Twitter, Facebook and YouTube. This method has also been implemented by Starbucks Indonesia as they realize they must utilize new media to complement their traditional way of marketing in creating positive perception among the young generation. Digital promotion by using applications such as LINE, Instagram and Twitter has helped generating interest among the millennials users in cultivating brand engagement prior to purchase. The data was collected using qualitative method of conducting a focus group discussion and a quantitative method of survey among the millennials in Jakarta between the age of 16 – 36 years old. Narrative analysis was used to analyze the findings of both the focus group discussion and the survey by applying literature review of consumer-brand engagement (Vivek, Beatty, & Morgan, 2011) and bandwagon (Neil, 2016). The data found that although Starbucks Indonesia has been engaging with its millennials consumers by way of digital promotion, it is solely a transactional engagement. They only used the digital advertisement solely to obtain promotional advantages. The study provides several recommendations that could be applied by Starbucks Indonesia to cultivate a long-lasting brand engagement with the millennials by way of digital promotion.